2020
DOI: 10.1093/gerona/glaa292
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance During the Menopausal Transition and the Role of Physical Activity

Abstract: Background To examine longitudinal changes in physical performance during the menopausal transition and the role of physical activity (PA) in these changes. Methods Based on follicle-stimulating hormone levels and bleeding diaries, women (47-55 years) were classified as early (n=89) and late perimenopausal (n=143) and followed prospectively until postmenopausal status, with mean duration of 17.5 and 13.8 months respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Handgrip strength measurement can be used as an indicator of general muscle strength among older people [ 54 ]. Maximal Nm was calculated from the best attempt measured in Newtons (N) multiplied by lower leg length (the distance between the lateral joint line of the knee and the midline of a cuff around the ankle) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Handgrip strength measurement can be used as an indicator of general muscle strength among older people [ 54 ]. Maximal Nm was calculated from the best attempt measured in Newtons (N) multiplied by lower leg length (the distance between the lateral joint line of the knee and the midline of a cuff around the ankle) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Age-associated decline in physical functioning that results in mobility limitations or disabilities among older people [7] may also be related to low mental well-being [8]. It has been shown that women who transitioned through perimenopause to postmenopause had a decline in muscle strength and muscle power on average by 2-3%, which may suggest that the decline in physical functioning accelerates already during midlife [9,10]. However, the physical performance of more physically active middle-aged women is greater than that of less physically active peers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Handgrip strength measurement can be used as an indicator of general muscle strength among older people [52]. Maximal Nm was calculated from the best attempt measured in Newtons (N) multiplied by lower leg length (the distance between the lateral joint line of the knee and the midline of a cuff around the ankle) [53].…”
Section: Methodsmentioning
confidence: 99%